An Educational Implementation Process Staff Survey: Lessons Learned. (May 2018) - Delmore, Barbara; Kent, Martha
ABSTRACT: OBJECTIVE: To evaluate the education process for the effective use of the Munro Pressure Ulcer Risk Assessment Scale by practicing perioperative staff at an urban tertiary medical center. Given that pressure injury formation is tied to the surgical process, there is a need for a pressure injury risk assessment scale that addresses the uniqueness of the perioperative process. METHODS: Participants were staff who worked in the surgical admissions area, the main operating room, and the main postanesthesia care unit. The authors' facility was 1 of 8 participants in a multisite study. Each site was required to educate staff using standard written instructions and an instructional webinar. However, sites were also encouraged to consider any other methods that would successfully engage the staff in the learning process. After the education process, staff were surveyed and asked to evaluate the educational interventions. MAIN RESULTS: Findings indicated that the staff did not prefer written instructions alone but rather preferred a combination of different learning modalities and media to assist them in using the Munro Scale effectively. CONCLUSIONS: This article discusses the strategies required to engage staff in the implementation process of this scale, the barriers encountered during this implementation, and the implications for perioperative nursing using this scale. The lessons learned from conducting this research provided insight into engaging and educating the adult learner in a new process.